Pelatihan Penyusunan Alat Evaluasi Berbasis Teknologi Informasi Dan Komunikasi ( Program Wondershare Quiz Creator) Untuk Guru SDN Airlangga I Surabaya - Iriyani, Dwi; Popiyanto, Yudha; Anshori, Sodiq (Penerbit LPPM- STKIP PGRI Bangkalan, 2019)
The community service program in the 2018 budget year was carried out with the aim of organizing community empowerment programs throughout the UPBJJ-UT region which included efforts to improve education and community welfare. Based on a description of the situation analysis of the partners/ assisted communities, the community service activities carried out were training in the development of information and communication technology-based evaluation tools (Wondershare Quiz Creator Program) for teachers of Airlangga I Elementary School in Surabaya. The implementation of this training activity is to provide understanding and skills on how to design and apply the wondershare quiz creator program in the development of evaluation tools for student learning outcomes. One of the targets to be achieved through community service activities is the change in attitude and improvement of the skills of partner communities so that the teachers of Airlangga I Elementary School Surabaya can develop evaluation tools for student learning outcomes using software wondershare quiz creator. The training was conducted with lecture methods, slide and video screenings, question and answer, interactive dialogue, opinion sharing and work practices.Community service activities as a whole are carried out in a span of 6 months (June - November 2018), starting from the planning, preparation, and implementation stages. In implementing community service, the team collaborated with lecturers from University of Wijaya Kusuma Surabaya namely the Language and Science Faculty as keynote speakers and instructors. The target community are teachers at Airlangga I Elementary School Surabaya and several teachers from Public and Private Elementary Schools from Gubeng District, Surabaya. The results of community service can be seen from the results of evaluating the processes, products, and participants' responses to the implementation of the training collected through the satisfaction questionnaire. In the process of implementing the training, partners generally have a great willingness and interest to take part in the training.